2017
DOI: 10.1016/j.biochi.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous effects of isomeric secondary amines containing an aromatic nitrile and nitro group on human aortic smooth muscle cells via inhibition of cystathionine-γ-lyase

Abstract: Excessive proliferation of vascular smooth muscle cells (SMC) is an important contributor to the progression of atherosclerosis. Inhibition of proliferation can be achieved by endogenously produced and exogenously supplied nitrogen monoxide, commonly known as nitric oxide (NO). We report herein the dichotomous effects of two isomeric families of secondary amines, precursors to the N-nitrosated NO-donors, on HASMC proliferation. The syntheses of these two families were carried out using two equivalents of homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We did blast the ENSBTAG00000004415 sequence against the cattle genome (ARS-UCD1.2) and found that the second exon of the ENSBTAG00000004415 was actually a retropseudogene of CTH in Bos taurus . Previous studies showed that both the CTH and the CTNNA1 functioned in the muscle cell differentiation [ 39 , 42 ]. We speculated that this CNV segment (chr7:50070412–50,072,341) may be related to the muscle development difference between Bos taurus and Bos indicus , through regulating ENSBTAG00000004415 and CTNNA1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did blast the ENSBTAG00000004415 sequence against the cattle genome (ARS-UCD1.2) and found that the second exon of the ENSBTAG00000004415 was actually a retropseudogene of CTH in Bos taurus . Previous studies showed that both the CTH and the CTNNA1 functioned in the muscle cell differentiation [ 39 , 42 ]. We speculated that this CNV segment (chr7:50070412–50,072,341) may be related to the muscle development difference between Bos taurus and Bos indicus , through regulating ENSBTAG00000004415 and CTNNA1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that both the Fig. 3 PCA analysis of the ten cattle breeds based on the CNV CTH and the CTNNA1 functioned in the muscle cell differentiation [39,42]. We speculated that this CNV segment (chr7:50070412-50,072,341) may be related to the muscle development difference between Bos taurus and Bos indicus, through regulating ENSBTAG00000004415 and CTNNA1.…”
Section: Possible Regulation Mechanism and Origin Of The Top Differenmentioning
confidence: 95%
“…Cystathionine gamma-lyase, CTH, has been detected as downregulated. CTH encodes an enzyme in the cellular processes of liver and kidney and it is a prognostic biomarker for bladder cancer [41]. CHAC1 has only been detected in the first and second periods of post-infection.…”
Section: Discussing the Relevance Of Extracted Key Genes Based On Thementioning
confidence: 99%